PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR PKNSISWAKELAS II SD NEGERI 101 KECAMATAN PAYUNG SEKAKI PEKANBARU - Nilmayati '; Zariul Antosa; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the lack of PKN student learning outcomes, as seen from the average value of students is 65.53. Of the 28 students who achieve grades above KKM just 10 students (35.70%), while students who have not reached the KKM many as 18 students (54.30%), the value specified KKM is 70. Based on these problems need to be done classroom action research to implement STAD cooperative learning. This research aims to improve learning outcomes PKN grade II SDN 101 Pekanbaru District of Umbrella Sekaki Academic Year 2014/2015. STAD cooperative learning model will motivate the students to encourage and to help each other among the students in mastering the skills or knowledge presented by the teacher. This classroom action research conducted by two cycles for all students in the class II A SDN 101 Pekanbaru District of Umbrella Sekaki totaling 28 people. At each cycle I and II consists of four sessions, which consist of two meetings face-to-face and twice daily test at the end of the meeting each cycle. With applied learning model type STAD cooperative, it can improve learning outcomes PKN grade II SDN 101 Umbrella SekakiPekanbaru District of SSchool Year 2014/2015, it is seen from the increase in student learning outcomes on the basis of grade II score, with an average of 65, 53 increased by 46.44% to 78.03 in the first cycle, and the second cycle of the elementary scores increased by 60.7% to 81.96. The percentage of teacher activity also increased, as seen from the percentage of the activity of teachers in the first cycle and the first meeting of the 79.16% rise in the second meeting becomes 87.50%, in the second cycle at the first meeting increased to 91.66%, and at the second meeting increased to 100%. The percentage of student activity also increased, as seen from the percentage of student activity in the first cycle of the first meeting 79.16% and maintained at the second meeting, namely 87.50%, in the second cycle at the first meeting increased to 91.66%, and the The second meeting increased to 100%. Based on the above it is concluded that the implementation of cooperative learning model type STAD can improve learning outcomes PKN grade II Elementary School District of Umbrella Sekaki 101 Pekanbaru.Keywords: Cooperative Learning Model STAD, PKN Learning Outcomes.2